Merrilliadione – a Rare Isopropyl (13→11)‐abeo‐9, 11‐seco Abietane Diterpene from Illicium merrillianum. Issue 22 (17th June 2014) - Tian, Xinhui; Yue, Rongcai; Zhang, Shoude; Shen, Yunheng; Ye, Ji; Shan, Lei; Li, Huiliang; Wen, Bo; Xu, Xike; Zhang, Weidong
Abstract: Merrilliadione (1 ), a new diterpene with a unique isopropyl (13→11)‐ abeo ‐9, 11‐ seco ‐abietane skeleton, and two new abietane diterpenoids (2 and3 ) were isolated from Illicium merrillianum . This is the first report of an isopropyl (13→11)‐ abeo ‐9, 11‐ seco abietane diterpenoid. The structures of1 –3 were established by comprehensive spectroscopic analysis, single‐crystal X‐ray diffraction, and quantum chemical computation of electronic circular dichroism (ECD) spectra. Abstract : Merrilliadione (1 ), a diterpene with a unique isopropyl (13→11)‐ abeo ‐9, 11‐ seco ‐abietane skeleton, and two the new abietane diterpenoids2 and3 were isolated from Illicium merrillianum . The structures of1 –3 were established by spectroscopic analysis, single‐crystal X‐ray diffraction, and quantum chemical computation of electronic circular dichroism (ECD) spectra.